2010
DOI: 10.2174/1874325001004010142
|View full text |Cite
|
Sign up to set email alerts
|

Perforation Rates of Cervical Pedicle Screw Insertion by Disease and Vertebral Level

Abstract: Background:Different perforation rates for cervical pedicle screws by disease are expected in relation to bone quality and pedicle morphology; however, no report comparing pedicle screw perforation rate by disease had previously been published. This study investigated the perforation rates of pedicle screws inserted to cervical pedicle by disease and vertebral level using a CT-based navigation system.Materials/Methods:Fifty-three patients who underwent cervical pedicle screw insertion using CT based navigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 20 publications
(19 reference statements)
0
23
0
1
Order By: Relevance
“…One of the reasons for very few studies [25262728] on kyphosis correction with CPS instrumentation in CSM is the relatively high incidence of CPS misplacements in CSM patients as compared to other pathologies. The perforation rates are reported to be about 37.5% [29]. Furthermore, the numbers of lateral perforations are reportedly twice that of medial perforations.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for very few studies [25262728] on kyphosis correction with CPS instrumentation in CSM is the relatively high incidence of CPS misplacements in CSM patients as compared to other pathologies. The perforation rates are reported to be about 37.5% [29]. Furthermore, the numbers of lateral perforations are reportedly twice that of medial perforations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients can stand up and walk shortly after treatment. In our study, this procedure maintained rigid fixation postoperatively and improved clinical symptoms [18]. However, CPS insertion is technically difficult because the cervical pedicle diameter is narrow, especially from C3 to 6.…”
Section: Discussionmentioning
confidence: 80%
“…Although the perforation rate in the present study is slightly higher than that reported previously, there were no serious complications. In our previous report comparing pedicle screw perforation rate with regard to the disease, the perforation rate for CSM was higher than those for spinal tumor, RA, and DSA [18]. However, strong deformities were observed, and pedicles sometimes became osteosclerotic in CSM patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In rheumatoid cervical spine, there is a severe destruction of the facet joints and most often the lateral mass is left with limited bony purchase. Therefore, the use of CPS is recommended as the strong initial fixation that eliminates the ne- cessity of postoperative external fixation such as halo vest or neck collar 32) . Hasegawa et al 28) evaluated the clinical results of patients with non-traumatic lesions treated using CPS.…”
Section: Clinical Indications Of Cpsmentioning
confidence: 99%